Comfort and antimicrobial properties of developed bamboo, polyester and cotton knitted spacer fabrics - Soares, Graça M. B. (2018)
3D space textile structures with different fibres composition were produced and evaluated in terms of breathability, thermal comfort and antimicrobial activity. Bamboo, cotton, polyester and bioactive polyester were applied to each fabric at proportions ranging from 14 to 72%. Out of the developed materials showing good mechanical and comfort properties, the knitted spacer fabric made up of bamboo and polyester showed the best global performance. The results of antimicrobial tests showed the importance of the contact area and the type of the bioactive agent for antimicrobial protection. Knitted spacer fabrics with 72% of antimicrobial fibres like bamboo were not active against the microorganisms tested where as knitted flatted fabrics made with the same yarn were effective against E. coli, P. aeruginosa and T. rubrum. Incorporation of thyme oil into the textiles imparted activity against E. coli, S. aureus, C. albicans and T. rubrum. The developed textiles have the potential to be used as footwear lining to prevent athlete's foot and associated bacterial infections.